The prophetic structure of 1-2 Samuel - Patrick, J (2016)
The book of 1-2 Samuel, originally one scroll, is an episodic narrative recounting how the ancient Israelite monarchy was established around 1000 BC by the prophet Samuel and the kings Saul and David. For well over a century historical critics have sought to discern the process of its composition, proposing various conclusions with little consensus. Presently it is generally believed that several blocks of traditional material on common themes (e.g. the History of David's Rise) were brought together in the later pre-exilic period as part of the so-called Deuteronomistic History. This thesis chooses to begin with the present limits of 1-2 Samuel (without including, for example, 1Kgs 1–2), and undertakes to apply rhetorical analysis to all fifty-five chapters, episode by episode, each in its final-form position. The particular structural technique that has been discerned throughout this book is inverted parallelism with an unparalleled centre, here termed 'concentrism'. The unique contributions of this thesis are firstly a careful methodology for concentrism in Hebrew narrative, based on Hebrew poetic and oral composition and proposing specific criteria for identifying and verifying such structures. Secondly, the thesis attempts to account for the current position of every episode in the book, discerning how each contributes to the larger work as regards literary structure and rhetorical message. The resulting arrangement demonstrates an overall unity of technique and authorial perspective, focused on the themes of prophecy (hence the thesis title), deliverance from military attack, religious devotion and dynastic succession. The centre of this thesis therefore provides a detailed description of the discovered structure, one chapter for each of the book's two primary segments (1Sam 1 – 2Sam 6; 2Sam 7–24). A lengthy preceding chapter addresses various theoretical issues often raised relating to such concentric patterns (often inadequately labelled 'chiasmus'/'chiastic'). A summary chapter likewise follows the central chapters, revisiting themes of the methodology and drawing conclusions together. An initial chapter outlines past and present compositional theories, and a concluding chapter suggests further avenues of future research.